Parent’s Role in Developing Children's English-Speaking Skills through Home-Based Language Learning - Yenni Christina (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study examines the critical role that parents play in assisting their children in improving their English-speaking abilities through language learning activities carried out at home using the Narrative Inquiry approach. The research aims to provide a thorough understanding of how parent-child interactions affect language development in addition to formal education. Recognizing the importance of the home environment, the study intends to illuminate the unique contributions parents make to their children's English proficiency, emphasizing the necessity of a thorough approach to language learning. Using in-depth interviews to gather rich, qualitative data, the main technique is narrative inquiry. Parents talk about their experiences and methods for encouraging English speaking in the family. This method enables a detailed investigation of the complex relationships and narratives that emerge in the setting of parent-child language development. Preliminary findings highlight a diverse range of home-based language learning activities, such as interactive dialogues, storytelling, reading English book, watching videos, using online applications, and language-rich routines. The narratives provide insights into the unique strategies parents employ to cultivate their children's language skills, revealing a profound impact on English-speaking abilities.  Therefore, parents play a crucial role in helping their children develop their English-speaking skills.